2001
DOI: 10.1073/pnas.221575398
|View full text |Cite
|
Sign up to set email alerts
|

The genome sequence of the facultative intracellular pathogen Brucella melitensis

Abstract: Brucella melitensis is a facultative intracellular bacterial pathogen that causes abortion in goats and sheep and Malta fever in humans. The genome of B. melitensis strain 16M was sequenced and found to contain 3,294,935 bp distributed over two circular chromosomes of 2,117,144 bp and 1,177,787 bp encoding 3,197 ORFs. By using the bioinformatics suite ERGO, 2,487 (78%) ORFs were assigned functions. The origins of replication of the two chromosomes are similar to those of other ␣-proteobacteria. Housekeeping ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
354
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 507 publications
(371 citation statements)
references
References 34 publications
(28 reference statements)
9
354
0
6
Order By: Relevance
“…The 1496 bp KpnI-SacI PCR fragment spanned a site located 25 bp upstream of the 5' end of znuA to a position 450 bp downstream from the 3' end [6] and amplified using primers 5'-GGTACCCCGGCTTGAGAATATGCAGCG-3' (KpnI site underlined) and 5'-GAGCTCCGTTGCCTGCCACG-GAAAGGG-3' (SacI site underlined).…”
Section: Meterials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1496 bp KpnI-SacI PCR fragment spanned a site located 25 bp upstream of the 5' end of znuA to a position 450 bp downstream from the 3' end [6] and amplified using primers 5'-GGTACCCCGGCTTGAGAATATGCAGCG-3' (KpnI site underlined) and 5'-GAGCTCCGTTGCCTGCCACG-GAAAGGG-3' (SacI site underlined).…”
Section: Meterials and Methodsmentioning
confidence: 99%
“…In Eschrerichia coli, two systems, a high-affinity system and a low-affinity system, have been described for zinc uptake [2,17], and the high-affinity zinc uptake system of Salmonella enterica serovar Typhimurium is important for virulence in mouse model [3]. However, B. abortus does not contain low-affinity zinc uptake system [6] and high-affinity zinc uptake system is still not understood.…”
mentioning
confidence: 99%
“…Distinction between species and biovars is currently performed by differential laboratory tests [3,27]. Although it has been proposed that the Brucella species should be grouped as biovars of a single species based on DNA-DNA hybridization studies [71] and on the comparison of the genome of B. melitensis [30] and B. suis [58], the current classification of brucellae in species according to differences in host preference and in pathogenicity should be preferred [23,53].…”
Section: Brucellae Taxonomymentioning
confidence: 99%
“…More recent study showed that BMEI0216 gene of B. melitensis is required for internalization in HeLa cells [14]. Essential genes encoding invasins and adhesins have been identified by Brucella genome analysis, but those molecules have not been investigated on Brucella surface [15]. Brucella LPS has been recognized as an important virulence factor involved in bacterial adhesion and internalization [16].…”
Section: Introductionmentioning
confidence: 99%